The Dialectic of Formalization - Germek, Magdalena (Filozofski vestnik, 2021)
This article discusses the philosophy of Alain Badiou from the perspective of a formulation that we believe represents it succinctly: the dialectic of formalization. The main thesis of the article is that Badiou’s doctrine of the four truth procedures (politics, science, love, and art) can be understood as a doctrine of a dialectical realization of new and universal forms in the world. The dialectic of formalization announces a double procedure – an autonomous and creative procedure for the production of a new true form in the world and a process of the formation of continuity in discontinuity. Moreover, the dialectic of formalization represents a connection between Badiou’s mature work and his early writings from the late 1960s. Even though in the 1960s and 1970s Badiou had not yet introduced the concepts of subject and truth in the sense that he understands them today, it is possible to support the thesis that there is an indisputable connection between Badiou’s early concept of formalization and his later concept of generic truth procedure. We will try to show that the dialectic of formalization (Badiou’s own formulation) designates the continuity between Badiou’s early and mature work.